Musculoskeletal injuries in musical arts professional : prevalence and determinants - Martins, Rosa (2018)
Background: Musculoskeletal injuries related to the work of professional musicians constitute a real public health problem. Objectives: To identify the prevalence of musculoskeletal injuries in professional musicians practicing plucked string instruments and to analyze their relationship with sociodemographic variables, health status and characteristics of instrumental practice. Methods: This was a non-experimental correlation, descriptive and quantitative character study, involving 140 Portuguese musicians living in 3 cities from Portugal, aged 18 to 55 years old. A questionnaire was used that included variables of sociodemographic characterization, health / style and musical practice. For the evaluation of musculoskeletal disorders we used the “Nordic Musculoskeletal Questionnaire”. Results: Of the musicians studied, 70.0% reported musculoskeletal disorders (MI) that manifested as pain / tingling / numbness in the last 12 months, mainly in the wrists / hands (68.6%) and shoulders (54.3%), We found that MI were more frequent in older musicians with higher Body Mass Indexes, those who consumed alcoholic beverages and did not practice physical activity, those who had excessive performances, those who used heavier instruments and took fewer breaks. Conclusions: The prevalence of MI in Portuguese musicians of plucked string instruments is high (70%) and these are related to individual characteristics, life styles and instrumental practice demands, which is urgent to modify through preventive measures.